(untitled) - Michael L. Walden (Englewood Cliffs, N.J., 1992)
A user-friendly look at how the practical tools of economic analysis can be used to make a multitude of everyday financial and consumer decisions, such as what mortgage is best and how much life insurance is necessary.
Keywords: Consumption (Economics),Consumer behavior,Mức tiêu thụ (Kinh tế),Hành vi tiêu dùng